Application of Lean Manufacturing to Minimize Waste in The Production Process of Tin Stabilizer - Novirani Dwi; Putri Zulkarnain Fitriani; Darrent Timotius (E3S Web of Conferences, 2024)
Lean Manufacturing concepts were being used by the manufacturing sector more and more in an eﬀort to maximize resource usage, cut costs, and increase eﬃciency. The research dived into the underlying concepts of Lean Manufacturing and its various tools and strategies for identifying and removing waste, such as overproduction, defects, needless inventory, wasteful motion, transportation, overprocessing, and waiting periods. Lean manufacturing methods could be implemented in the continuous manufacturing environment to detect and reduce waste by using a process flow chart, value stream mapping tools, waste assessment model, value stream analysis tools, and the 5 why’s method. According to the findings of the study, the most prevalent waste in the manufacturing process was waste flaws, delays, and wasteful inventory. Process activity mapping (PAM), one of VALSAT’s extensive mapping technologies, was used to eliminate waste. The lead time was reduced by 12 days and 1 hour as a consequence of the improvement recommendations study. NVA activity was reduced from 75.3% to 59.5% based on the PAM study. Reduced lead time could result in a more eﬃcient production process and lower production costs.